APPLICATION FOR TERMINATION OF EMPLOYMENT BY WORKERS / LABORERS BECAUSE THEY ARE LAID OFF WITHOUT WAGES MORE FROM MOON - Hermanto, Joni; Rum, Rumainur (Transnational Business Law Journal, 2024)
Government in November 2020 passed Law Number 11 of 2020 concerning Job Creation, then in February 2021 the Government stipulated implementing regulations from Law Number 11 of 2020, namely Government Regulation Number 35 of 2021 concerning Certain Time Work Agreements, Outsourcing, Working Time, and Rest Time, and Termination of Employment. On March 11, 2020, the world health organization World Health Organization (WHO) declared COVID-19 as a Global Pandemic, and on April 13, 2020, the Government of Indonesia issued a Presidential Decree of the Republic of Indonesia Number 12 of 2020 concerning the Determination of Non-Natural Disasters for the Spread of Corona Virus Disease 2019 (COVID-19) as National Disasters. People infected with the Covid-19 outbreak every day continue to increase, as well as the number of deaths due to the Covid-19 outbreak continues to grow. The Central Government and the Dareah Government issued policies to prevent and overcome the spread of the COVID-19 outbreak, namely by implementing Large-Scale Social Restrictions (PSBB) and the Implementation of Community Activity Restrictions (PPKM). With the existence of PSBB and PPKM by the Government, several sectors, especially the accommodation provision sector, tourism business, food and beverage business, real estate, and construction, have experienced a direct impact as a result of the Covid-19 pandemic and the existence of PSBB and PPKM. The tourism sector, especially hotels, has experienced a decrease in income due to the lack of guests staying, forcing employers to lay off their workers/workers without providing wages to reduce expenses and save company finances. This thesis research analyzes the impact arising from workers/workers being laid off without being given wages and legal considerations on the decision of the Industrial Relations Court at the Central Jakarta District Court with case number: 398 / Pdt. Sus PHI / 2021 / PN. JKT. PST. The purpose of this decision analysis is to find out the Request for Termination of Employment (PHK) by Workers / Workers because they were laid off for more than three months without wages based on Law Number 11 of 2020 concerning Job Creation.